2021
DOI: 10.3390/ijerph18116061
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Network Size and Contact Frequency on Resilience in Community-Dwelling Healthy Older Adults Living Alone in the Republic of Korea

Abstract: The aim of this study was to investigate the characteristics of social health and its association with resilience among older adults living alone excluded from the public care service due to their relatively good health. For this cross-sectional study, we surveyed older adults aged between 65 and 80 years using questionnaires to measure the social health status and levels of resilience of the participants. We conducted a hierarchical regression analysis to confirm the association between resilience and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
6
0
3
Order By: Relevance
“…In addition, we examined the association of social support and social network with resilience. Previous research found that both variables were associated with resilience [ 14 , 23 , 25 , 26 , 27 ]. Until now, it has been unclear how these variables are associated with resilience when controlled for each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we examined the association of social support and social network with resilience. Previous research found that both variables were associated with resilience [ 14 , 23 , 25 , 26 , 27 ]. Until now, it has been unclear how these variables are associated with resilience when controlled for each other.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research identified social support as a relevant resilience resource in particularly burdened individuals [ 14 , 23 , 24 , 25 ]. In addition, Park et al [ 26 ] and Wells [ 27 ] found that a larger social network was associated with higher resilience in older adults. Social variables like social support and social network are strongly interdependent and might have overlapping influences in the prediction of mental health outcomes [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large part of recent research concentrates on the personal social network (or egocentric network), that is, the specific collection of social ties that are most meaningful to a given person (Cornwell et al 2009). Different aspects of the social network are variously related to outcomes of gerontological interest, such as life satisfaction (Rafnsson et al 2015), resilience (Park et al 2021), psychological distress (Phongsavan et al 2013) and mortality (Ellwardt et al 2015;Lund et al 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Soziale Ressourcen hängen maßgeblich mit der selbstberichteten Resilienz zusammen [ 27 ]. Erste Studien in anderen Ländern zeigen eine hohe Bedeutsamkeit von sozialen Ressourcen für selbstberichtete Resilienz in älteren Stichproben [ 28 , 29 ]. Inwieweit die Befunde dieser Studien auf die deutsche Altenbevölkerung übertragbar sind, ist unklar, da die Bedeutung sozialer Kontakte auch von der jeweiligen Kultur abhängt [ 30 ].…”
Section: Introductionunclassified